Relationship between fibroblast growth factor 21 and thyroid stimulating hormone in healthy subjects without components of metabolic syndrome. Issue 3 (1st September 2014) - Fu, Tianxu; Yuan, Shanshan; Gao, Ying; Qu, Chenxue; Chen, Lan; Hui, Yan; Lu, Guizhi; Gao, Yanming; Guo, Xiaohui
Abstract : Objective: To determine the relationship between human fibroblast growth factor 21 (FGF21) and thyroid stimulating hormone (TSH) by testing the level of FGF21, lipid metabolism, and carbohydrate metabolism-related indices, as well as the level of TSH, among metabolic syndrome-free patients with normal physical examination results. Methods: An enzyme-linked immunosorbent assay (ELISA) was used to test the levels of serum FGF21 and free fatty acids (FFA) in metabolic syndrome-free patients with normal physical examination results, and electrochemiluminescence (ECLIA) was used to measure TSH, thyroglobulin antibodies (TGAbs), and thyroid peroxidase antibody (TPOAb) levels. Results: Three hundred fifty-six metabolic syndrome-free patients (116 males and 240 females; average age, 43±13 years) with normal physical examination results were enrolled. Among the patients with normal physical examination results, FGF21 had a weak relationship with obesity indices, such as the waist circumference (r=0.110, P =0.038), the waist-to-hip ratio (r=0.119, P =0.025), and the triglycerides level (TG; r=0.302, P =0.000), and a weak relationship with blood lipid levels, such as total cholesterol (TCHO; r=0.113, P =0.012) and low-density lipoprotein-cholesterol (LDL-C; r=0.175, P =0.001), but no relationship with TSH (r=–0.023, P =0.666). In addition, the FGF21 levels in thyroid autoantibody-positive and -negative groups were not significantly different. Conclusion: Among the metabolic syndrome-free patients with normal physical examination results, FGF21 has no apparent relationship with TSH or thyroid autoimmunity.